Islamic Legal Perspective on Cybercrime: An Ethical and Legal Analysis of Contemporary Challenges in Digital Responsibility: Islamic Legal Perspective on Cybercrime - Muhammad Ruslan Afandi (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
Cybercrime is getting more and worse in Indonesia, affecting people, society, and the security of the country. This paper examines several forms of cybercrime through the lens of Islamic law, which is regarded as a violation of the principles of justice, honesty, and the prohibition of wrongdoing. This study employs a descriptive qualitative methodology, utilizing secondary data from BSSN, Kominfo, UNICEF, Mafindo, and scholarly publications from 2020 to 2025. The process of gathering data involved looking at papers and putting them into groups based on themes to find patterns, trends, and social-legal effects. The research results show that the number of cases and damages goes up every year, mostly because of internet fraud and data breaches. Islamic law views cybercrime as a breach of the tenets of justice, integrity, and the prohibition of immoral conduct. Islamic law emphasizes the significance of digital ethics and individual accountability in the virtual realm, hence enhancing preventive measures and cultivating a refined digital society. This research has important effects on public policy, showing that we need to combine laws, educational programs, and moral standards to make cybersecurity stronger. This study promotes ongoing policy evaluation, the integration of religious ethical concepts into digital education, and the enhancement of international cooperation.Keywords: cybercrime, islamic law, and digital responsibility